ANALYSIS OF THE USE OF QRIS ON CONSUMER BEHAVIOR AT CAFÉ LATHOMAN - Himami Firdausi; Miftahul Arifin (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2026)
This study aims to analyze the effect of the use of the Indonesian Standard Quick Response Code (QRIS) on consumer behavior at Café Lathoman. The research method used was descriptive qualitative, with data collection techniques through in-depth interviews and observations of ten STEBI BAMA students who were customers of Café Lathoman on September 25, 2025. The results show that the use of QRIS provides convenience and efficiency in financial transactions, as well as increasing consumer convenience. However, this convenience also encourages consumptive behavior due to a decreased perception of the value of money. Thus, the use of QRIS has a dual impact: on the one hand, it increases transaction effectiveness, and on the other hand, it creates psychological challenges in the form of a tendency to overconsume among students.